Proportional step perturbation method MPPT for boost circuit of TEG - Ji, Feng; Xu, John (Springer, 2020)
In order to improve the working efficiency of thermoelectric generation (TEG), maximum power point tracking (MPPT) is usually used in the system. The perturbation method is a traditional method for MPPT. The perturbation of the step length is normally fixed. It will lead to be not accurate enough if the step size is too big. If the step size is too small, it will lead to take a long time. Therefore, the proportional step perturbation method MPPT is proposed in the paper. This method can be implemented by using large steps at the beginning to save time. When it is near the maximum power point, small steps can be used to achieve the accurate purpose. The derivation of the method has been described in details in the paper. The simulation model is established based on Matlab. The simulation results show that the method is feasible.